Evaluating the Effects of Sodium Diformate on Finishing Pig Growth Performance - Katelyn N. Gaffield; Mike D. Tokach; Robert D. Goodband; Jason C. Woodworth; Joel M. DeRouchey; Jordan T. Gebhardt; Mariana B. Menegat; Mary Liebenstein; Matt Allerson (Kansas Agricultural Experiment Station Research Reports, 2023)
A total of 2,200 pigs (Duroc sire (PIC 800 or DNA 600) × PIC Camborough; initially 53.4 ± 0.66 lb) were used to conduct a 117-d growth trial to evaluate the effects of dietary sodium diformate level on grow-finish pig growth performance and carcass characteristics. Pens of pigs (25 pigs per pen) were randomly assigned to 1 of 4 dietary treatments in a randomized complete block design with 22 replicates per treatment. Dietary treatments were corn-soybean meal-based with the addition of none, 0.25, 0.50, or 0.75% sodium diformate (Formi NDF; ADDCON Nordic AS, Porsgrunn, Norway). Diets were fed in 6 phases from 53 to 75, 75 to 145, 145 to 195, 195 to 245, 245 to 265, and 265 to 310 lb. From d 60 to 93, increasing sodium diformate increased (linear,P<0.01) ADG and ADFI. Additionally, from d 93 to 117, increasing sodium diformate in the diets increased (linear,P<0.05) ADG, ADFI, and improved (linear,P<0.05) feed efficiency. For the overall period (d 0 to 117), pigs fed increasing sodium diformate had increased (linear,P<0.01) ADG and a tendency for increased (linear,P= 0.075) ADFI; however, there was no evidence for differences (P>0.05) in feed efficiency. For carcass characteristics, no evidence of differences (P>0.10) was observed for any criteria. For economics, increasing sodium diformate in the diets increased (linear,P<0.001) feed cost and feed cost per lb of gain in both low and high price scenarios. However, there was a tendency for a quadratic effect (P= 0.059) for revenue, with pigs fed 0.25% sodium diformate generating the greatest revenue in both the low and high price scenarios. Due to the increased feed cost and quadratic response in revenue, pigs fed increasing sodium diformate had a quadratic (P<0.05) response in IOFC, with pigs fed no sodium diformate having the greatest IOFC. In conclusion, these data suggest that feeding increasing levels of sodium diformate improved ADG and ADFI after d 60 (~180 lb) in the grow-finish period. However, it is currently not economical to feed sodium diformate throughout the entire grow-finish period.
Keywords: acidifier; finishing pig; growth performance; sodium diformate